Orthopedic Emergencies - Makhni, Melvin C.; Makhni, Eric C.; Swart, Eric F.; Day, Charles S. (Springer International Publishing : Imprint: Springer, 2017)
This book is a one-stop guide to managing acute orthopedic injuries. Unlike other handbooks, this reference provides a comprehensive, yet concise, set of diagnostic and management tools to help readers deliver optimal, evidence-based, and efficient patient care. Additional focus on physical exam techniques, emergency room orthopedic procedures, and on-field athletic management strategies empowers readers with real tips and tricks used by orthopedic surgeons at top-tier institutions. This guide is a must have for emergency medicine providers, orthopedic surgeons, and other clinicians, trainees, and students caring for adult or pediatric patients in the emergency setting. .
Keywords: Medicine.; Emergency medicine.; Orthopedics.; elektronické knihy; electronic books